The impact of pharmacy benefit managers on community pharmacy: A scoping review - Meagen Rosenthal; Lindsey Miller; Mixson Bateman; Megan Smith; Katrina Nueva; Jordan M. Ballou (Elsevier, 2023)
Introduction: The introduction of pharmacy benefit managers (PBMs) within the United States healthcare system occurred with the aim to decrease costs and increase quality. News media and legislation have painted a picture of decreased pharmacy competition and potential negative impacts on patients and their access to affordable medications. Objective: The objective of this scoping review was to evaluate the current research literature examining the impact of PBMs on the finances of community pharmacies. Methods: Scientific journal articles published between 2010 and 2022 were included if they met the predefined objective. Results: This scoping review identified four articles that met inclusion criteria. None of the identified articles independently quantified the financial impact of PBMs on community pharmacies. Conclusions: Additional research should be completed to specifically understand the financial impact on community pharmacies to help ensure the viability of community pharmacy as an integral access point for patients.